2015
DOI: 10.1186/s12902-015-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between microvascular complications and vitamin D deficiency in type 2 diabetes mellitus

Abstract: BackgroundVitamin D deficiency is reported as a possible risk factor for the development of diabetes in several epidemiologic studies. In this study, we investigated the frequency of 25-OH vitamin D deficiency in type 2 diabetes mellitus and the relationship between 25-OH vitamin D deficiency and the prevalence of microvascular complications.MethodsIn this retrospective study, we evaluated the medical records of 557 patients with type 2 diabetes admitted to the Endocrinology Outpatient Clinic from January to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 34 publications
2
35
3
2
Order By: Relevance
“…A number of studies have compared 25(OH)D concentrations between groups of individuals with and without diabetic retinopathy in case–control designs [3, 11, 13, 17, 22] with a protective association of 25(OH)D on prevalent retinopathy found in three studies [3, 11, 13]. The majority of other studies consist of cross-sectional designs recruiting participants from clinical settings [5, 6, 9, 10, 12, 14, 15, 19, 21, 23] with half of these studies supporting a protective association of vitamin D with retinopathy [5, 6, 9, 10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared 25(OH)D concentrations between groups of individuals with and without diabetic retinopathy in case–control designs [3, 11, 13, 17, 22] with a protective association of 25(OH)D on prevalent retinopathy found in three studies [3, 11, 13]. The majority of other studies consist of cross-sectional designs recruiting participants from clinical settings [5, 6, 9, 10, 12, 14, 15, 19, 21, 23] with half of these studies supporting a protective association of vitamin D with retinopathy [5, 6, 9, 10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…[11] In view of these observations, we hypothesize that vitamin D could be linked to CVD through the presence of a microvascular component. Studies investigating the link between vitamin D and indices of microvascular disease have shown that vitamin D deficiency was associated with poor coronary microcirculation, [12] endothelial dysfunction, [13] nephropathy, [14] and with markers of cerebral small-vessel disease. [15] Although these studies suggest a microvascular component in the link of vitamin D with CVD, no study has investigated the direct relation of vitamin D with markers of microvascular damage in humans.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Tahrani and colleagues [19] and Usluogullari and colleagues [20] found no difference in the prevalence of vitamin D deficiency between diabetic peripheral neuropathy patients and controls. The contradiction between such results and our findings can be explained by, first, using different methods for diagnosis of peripheral neuropathy (they only used monofilament and vibration) and, second, neurophysiological tests had not been done.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, there was no significant relation between the level of HbA1c and serum vitamin D level. Similarly, Olt [30] and Usluogullari and colleagues [20] failed to detect a relationship between HbA 1c and serum 25-OH vitamin D levels and stated that HbA1C levels were similar across groups with different 25-OH vitamin D concentrations.…”
Section: Discussionmentioning
confidence: 99%